The judgment in the Intel case or how Competition law does not respond to the current reality - Zurimendi Isla, Aitor (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The judgment of the General Court of 26.1.2022 overrides the Decision of the Commission in the Intel case and establishes a system of distribution of the burden of proof that in practice supposes a great obstacle for the Competition Authorities to stop effectively the abuse of dominant position of digital companies. This paper analyzes the sentence, the ideal model of the burden of proof system for the abuse of dominant position, and proposes its reform.
Keywords: abuse of dominant position; burden of proof; Competition law